THE EFFECT OF FRIENDSHIP CIRCLE ON RELIGIOSITY IN STUDENTS - Indah Septiani; Mustika Marlina; Afifha Ramandhini; Siti Hasmiah; Saputra Agung Suroji (Journal of Psychology and Social Sciences, 2023)
The purpose of this study was to determine the effect of friendship circles on religiosity in 2nd and 4th semester students at the Faculty of Psychology, State Islamic University Raden Fatah Palembang. the research method used in this research is quantitative using comparative causal techniques. The subjects of this study were 2nd and 4th semester students at the Faculty of Psychology, State Islamic University Raden Fatah Palembang. The sample of this study were 33 students who were taken using a questionnaire. The instrument used is the friendship circle scale and the religiosity scale. The results of the hypothesis test (product moment) show a very high level of relationship, there is a real (significant) influence of variable X (friendship) on variable Y (religiosity). From the output it can be seen that F count = 9,722 with a significance level or probability of 0.004 <0.05, the regression model can be used to predict the religiosity variable.